HUBUNGAN ANTARA HUKUM DENGAN MORAL DALAM ISLAM - Syarifuddin Syarifuddin (IAIN Ambon, 2017)
Law and morals have relationship like spirit and physic. One of them becomes meaningless if it ignores the other. Islam makes the law as a tool to create servant obedience to his Creator. This obedience will bear moralized or characterized servant against each other, to the environment and also to his God. Islam as rahmatan lil 'alamin religion never separates are both. Because the law without moral law is tyranny, while moral without the law is anarchy and utopia that lead to animalistic character. Key words: Legal, moral, maslahat and mafsadat